The scanning of hadronic cross-section in e⁺e⁻-annihilation by radiative return method - Konchatnij, M.I.; Merenkov, N.P.; Shekhovtsova, O.N. (Вопросы атомной науки и техники, 2001)
The possibility of high precision measurement of the total hadronic cross-section in electron-positron annihilation process by analysis of the initial-state radiative events is discussed. Different experimental setups are discussed. The main attention is dedicated to measurement of hadronic cross-section at DAPhNE, where the final hadronic state π⁺π⁻ dominates due to radiative return on ρ-resonance. Radiative corrections at one percent level accuracy are calculated taking into account real experimental constraints on event selection.